Two Accounts – One Ascension: Luke 24:50-53 and Acts 1:9-11 - Wasiak, Wojciech (The Biblical Annals, 2022)
This article investigates the ascension accounts (Luke 24:50-53 and Acts 1:9-11) in a narrative way. The main analysis point will be the question: why is one event recounted twice: at the end of the first Lukan volume and the beginning of the second? The second question concerns the meaning of the discrepancies between the two pericopes. We argue that all differences can be explained by Luke’s literary and narrative strategy. Luke 24:50-53 recounts the recognition of Jesus. Acts 1:9-11 marks the end of the period (between resurrection and ascension) needed for the disciples to become the legitimate and authoritative successors of Jesus.